What alleviates depression among medical workers in emergency risk events? The function of subjective social status. Issue 3 (March 2023) - Tan, Xuyun; Lv, Miao; Fan, Lingxia; Liang, Yuan; Liu, Jiayin
Abstract: Medical workers often face serious family-work conflicts and are prone to depressive symptoms. The present study aimed at investigating associations between family-work conflict and depression in emergencies, and at exploring psychological processes involved in this association. A total of 1347 participants were recruited to complete questionnaires. Results showed that the positive effect of family-work conflict on depression was mediated by the basic psychological needs satisfaction, and subjective social status moderated this relationship as a buffer. For individuals with high levels of subjective social status, the direct and indirect effects of family-work conflict on depression were weaker. This study identified the mediating and moderating mechanisms of family-work conflict and depression. The implications of these findings in both theoretical and practical terms will be discussed. Highlights: Family-work conflict had a positive predictive effect on depression. Basic psychological needs satisfaction plays a mediating role. SSS negatively moderated the mediating role of basic psychological needs satisfaction. For individuals with high levels of SSS, family-work conflict had a weak positive effect on depression.